ANALISIS METODE K-MEANS PADA PENGELOMPOKAN PERGURUAN TINGGI MENURUT PROVINSI BERDASARKAN FASILITAS YANG DIMILIKI DESA - Muhammad Aliyul Amri; Agus Perdana Windarto; Anjar Wanto; Irfan Sudahri Damanik (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Higher education is an education level that includes diplomat, undergraduate and doctoral programs. The purpose of higher education is to improve the quality of the workforce, to help improve the quality of the workforce each university must have the facilities needed in teaching and learning activities. This study discusses the Analysis of the K-Means Method in the Grouping of Universities by Province Based on the Facilities of the Village. Sources of data obtained from data collected based on documents from 2003 to 2018 through the website of the Indonesian Statistics Agency. Data is processed into 2 clusters, namely the highest facility level cluster (C1) and the lowest facility level cluster (C2). So that obtained from 34 provinces 3 provinces are grouped in high facility level clusters (C1) and 31 provinces are grouped in low facility level clusters (C2). This can be input to the government for provinces that have higher education institutions that still have inadequate facilities in each village and are of more concern to the government based on the cluster that is being conducted.Keywords: K-Means, Higher education, Grouping, Facilities